The impact of the Hsp67Bc gene product on Drosophila melanogaster longevity, fecundity, and acute heat stress tolerance - D. Malkeyeva; S. A. Fedorova; E. Kiseleva (Вавиловский журнал генетики и селекции)
Drosophila melanogaster Hsp67Bc is a heat- and cold-inducible small heat shock protein that participates in the prevention of aggregation of misfolded proteins and in macroautophagy regulation. Overexpression of the Hsp67Bc gene has been shown to enhance macroautophagy in Drosophila S2 cells, and the deletion of this gene leads to the formation of a slightly increased number of autophagic vacuoles in the fruit f ly brain neurons. Recently, we found that Hsp67Bc-null D. melanogaster f lies have poor tolerance to cold stress (0 °C) of various durations. In the present work, we investigated how the Hsp67Bc gene deletion affects the f itness of fruit f lies under normal conditions and their tolerance to elevated temperatures at different developmental stages. Larvae and pupae were not adversely affected by the Hsp67Bc gene deletion, and adult Hsp67Bc-null f lies showed an extended lifespan in comparison with the control at normal (24–25 °C) and elevated temperature (29 °C), and after acute heat stress (37 °C, 2 h). At the same time, the fecundity of the mutant females was lower by 6–13 % in all tested environments, except for permanent maintenance at 29 °C, where the mean numbers of eggs laid by the mutant and control f lies were equal. We explain this phenomenon by a reduced number of ovarioles in Hsp67Bc-null females and enhanced macroautophagy in their germaria, which promotes the death of forming egg chambers. In addition, short heat stress (37 °C, 2 h), which increased the control line’s longevity (an effect common for a wide range of organisms), had a negative impact on the lifespan of Hsp67Bc-null f lies. Therefore, Hsp67Bc-null D. melanogaster have an extended lifespan under normal and elevated temperature conditions, and reduced fecundity and thermal stress tolerance.